2013
DOI: 10.3168/jds.2013-6903
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring mastitis disrupts developmental competence of bovine oocytes

Abstract: We examined the effects of naturally occurring mastitis on bovine oocyte developmental competence in vitro. Specifically, we investigated the effects of intramammary infection on the ovarian pool of oocytes (i.e., follicle-enclosed oocytes) and their ability to undergo in vitro maturation, fertilization, and further development to the blastocyst stage. Culled Holstein cows (n=50) from 9 commercial dairy farms in Israel were allotted to 3 groups according to somatic cell count (SCC) records of the last 3 monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 32 publications
6
28
0
3
Order By: Relevance
“…In particular, a past clinical event occurring up to 10 days prior to AI significantly reduced the probability of conception. Furthermore, we have recently shown that E. coli mastitis occurring during a 90-day period prior to performing IVM/IVF disrupts the ovarian pool of GV stage oocytes, resulting in a decrease in blastocyst formation rate (Roth et al 2013). Taken together, the findings support the view that not only the developing embryo but also the oocyte is highly susceptible to pathogenic (mastitis) stress.…”
Section: Discussionsupporting
confidence: 77%
“…In particular, a past clinical event occurring up to 10 days prior to AI significantly reduced the probability of conception. Furthermore, we have recently shown that E. coli mastitis occurring during a 90-day period prior to performing IVM/IVF disrupts the ovarian pool of GV stage oocytes, resulting in a decrease in blastocyst formation rate (Roth et al 2013). Taken together, the findings support the view that not only the developing embryo but also the oocyte is highly susceptible to pathogenic (mastitis) stress.…”
Section: Discussionsupporting
confidence: 77%
“…The same study revealed a negative correlation between systemic LBP and serum progesterone, similar to what was observed in this study (Tremellen et al 2015). In dairy cows, bacterial infections of the mammary gland result in altered steroidogenesis, ovarian function, and oocyte quality following natural or induced disease (Lavon et al 2008, Roth et al 2013, Asaf et al 2014.…”
Section: Discussionsupporting
confidence: 69%
“…The proportion of oocytes that developed to blastocysts was lower in those obtained from the high SCC versus controls cows. The study showed for the first time that mastitis (diagnosed as clinical or subclinical) impairs oocyte developmental competence and that the ovarian pool of oocytes at the GV stage is vulnerable to this disease [89]. However, the reason for this susceptibility is unclear.…”
Section: Effect Of Mastitis On the Oocytementioning
confidence: 99%
“…Cows were defined as clean or mastitic based on SCC records and bacteriology diagnosis within 3 mo before oocyte collection [89]. The proportion of oocytes that developed to blastocysts was lower in those obtained from the high SCC versus controls cows.…”
Section: Effect Of Mastitis On the Oocytementioning
confidence: 99%